A Cross-Sectional Study of Medication Adherence Pattern and Factors Affecting the Adherence in Chronic Obstructive Pulmonary Disease - Shrestha, R; Pant, A; Shakya Shrestha, S; Shrestha, B; Gurung, RB; Karmacharya, BM (Kathmandu University Medical Journal, 2015)
Background Chronic obstructive pulmonary disease (COPD) is considered as a major health problem, associated with mortality and morbidities. Various disease management strategies have been established to optimize patient’s longevity and functional status where patient adherence to the prescribed treatment plays a key role. Poor adherence to medication is common among COPD patients and is affected by number of factors like number of medicines, delivery devices and patient-related factors. Objective This study aims to investigate the adherence pattern in the management of COPD and factors affecting patient adherence to the prescribed treatment. Method This study is a cross-sectional study which was conducted in a tertiary care hospital. Those patients suffering from COPD of all age were enrolled in this study and prior informed consent was obtained from patients. The structured questionnaire was used to interview those patients. Result Total 100 patients were enrolled in this study, among which most patients (45%) were of age groups 60-70 years. Unintentional non-adherence to medication attributed for 65% of patients and the major reason was forgetfulness (52.3%). Most patients had discontinued the medication due to experience of side effects (63.3%). The result showed significant association between adherence and polypharmacy (p=0.00). However, there was no significant association between adherence and age, sex, mode of administration of drugs, technics to use delivery devices etc. Conclusion Majority of COPD patients were elderly (mean age= 68.4 years). Forgetfulness was associated with medication non-adherence. Most of the patients had discontinued medication because of side effects. Polypharmacy is one of the major factors associated with non-adherence to medication in COPD. Kathmandu University Medical Journal Vol.13(1) 2015; 64-70